Stress During Pregnancy and Epigenetic Modifications to Offspring DNA: A Systematic Review of Associations and Implications for Preterm Birth. Issue 2 (April 2020) - Nowak, Alexandra L.; Anderson, Cindy M.; Mackos, Amy R.; Neiman, Emily; Gillespie, Shannon L.
Abstract : Offspring born preterm (ie, before 37 weeks of gestation) are more likely to die or experience long-standing illness than full-term offspring. Maternal genetic variants (ie, heritable, stable variations in the genetic code) and epigenetic modifications (ie, chemical modifications to the genetic code that can affect which genes are turned on or off) in response to stress have been implicated in preterm birth. Fetal genetic variants have been linked to preterm birth though the role of offspring epigenetics in preterm birth remains understudied. This systematic review synthesizes the literature examining associations among stress during pregnancy and epigenetic modifications to offspring DNA, with 25 reports identified. Ten reports examined DNA methylation (ie, addition/removal of methyl groups to/from DNA) across the epigenome. The remainder examined DNA methylation near genes of interest, primarily genes linked to hypothalamic-pituitary-adrenal axis function ( NR3C1, FKBP51 ), growth/immune function ( IGF2 ), and socioemotional regulation ( SLC6A4, OXTR ). The majority of reports noted associations among stress and offspring DNA methylation, primarily when perceived stress, anxiety, or depression served as the predictor. Findings suggest that differences in offspring epigenetic patterns may play a role in stress-associated preterm birth and serve as targets for novel interventions.